Testing protocol for evaluating underhand serve-reception biomechanics in volleyball - Callupe, R.L.; Chau, J.M.; Garcia, J.G.; Chicoma, C.G.; Arrese, C.F.; Artieda, M.H.; Elías, D.A.; Villota, E. (SAGE Publications, 2025)
A testing protocol for conducting biomechanical underhand serve-reception evaluation in volleyball in match-like conditions is presented. A launcher sends a ball over the net toward the reception zone for the player to pass it to the setter; the ball is tracked with video cameras and the player’s articular information is captured by inertial sensors, force plates, and video cameras. Test-retest reliability and, known-groups and concurrent validity of the test are evaluated. Left knee, right knee, left shoulder, and right shoulder angles were highly reliable (ICC > 0.88), with low standard errors of measurement (%SEM < 13.07). Resultant normalized ground reaction forces were also reliable (ICC: 0.76, %SEM: 9.14). Professional and amateur athletes’ comparisons were statistically significant and non-trivial (p < 0.05, Cohen’s d > 0.49), with professionals’ body movements presenting small variance and symmetry between left and right limb variables, and amateurs’ presenting higher variance and greater asymmetry. Finally, each athlete’s left limb angles were compared against their corresponding sagittal Kinovea measurements for concurrent validity, obtaining acceptable correlation scores for amateur athletes (PCC > 0.79) and good correlation scores (PCC > 0.83) for professional athletes. The test offers a reliable and valid method for evaluating underhand serve-reception biomechanics in volleyball players.
Keywords: Biomechanics; Sports biomechanics; Physical medicine and rehabilitation; Sagittal plane; Amateur; Accelerometer; Athletes; Simulation; Physical therapy; Psychology; Mathematics; Computer science; Medicine; Anatomy; https://purl.org/pe-repo/ocde/ford#3.02.00